2020
DOI: 10.1007/s00068-020-01381-6
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury and alcohol intoxication: effects on injury patterns and short-term outcome

Abstract: Purpose A significant number of patients with traumatic brain injuries (TBI) are diagnosed with elevated blood alcohol concentration (BAC). Recent literature suggests a neuroprotective effect of alcohol on TBI, possibly associated with less morbidity and mortality. Our goal is to analyze the association of different levels of BAC with TBI characteristics and outcome. Methods Adult patients with moderate to severe TBI (AIS ≥ 2) and measured BAC admitted to the Trauma Centre West (TCW), during the period 2010–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There is growing evidence from human studies on the effect of alcohol in persons with TBI on mortality, given the metabolic and neurological effects of alcohol 33 . Several populationbased cohort studies reported that alcohol intoxication at the time of injury was not associated with in-hospital or long-term mortality or improved survivorship, taking into account TBI severity, age and sex 34,35,36 ; one study 37 reported the opposite -that alcohol intoxication increases risk of mortality. Such discrepancies may be due to the numerous dose-related effects of alcohol, the time of exposure in relation to the injury, temporary versus continuous effects 38 , or genetic susceptibility 39 .…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence from human studies on the effect of alcohol in persons with TBI on mortality, given the metabolic and neurological effects of alcohol 33 . Several populationbased cohort studies reported that alcohol intoxication at the time of injury was not associated with in-hospital or long-term mortality or improved survivorship, taking into account TBI severity, age and sex 34,35,36 ; one study 37 reported the opposite -that alcohol intoxication increases risk of mortality. Such discrepancies may be due to the numerous dose-related effects of alcohol, the time of exposure in relation to the injury, temporary versus continuous effects 38 , or genetic susceptibility 39 .…”
Section: Discussionmentioning
confidence: 99%